Research progress on analysis and test methods of aircraft panel flutter - HE Chuanyang; WANG Binwen; SONG Qiaozhi; LI Xiaodong; CHEN Haoyu (Hangkong gongcheng jinzhan)
Aircraft panel flutter is a typical aeroelastic stability problem that occurs during supersonic flight，and is characterized by aerodynamic unilateral effects and significant structural and aerodynamic nonlinearity. The current research status of panel flutter issues both domestically and abroad is reviewed from the perspectives of flutter analysis methods and experimental techniques in this paper. The commonly used technical means for panel flutter analysis and testing in the engineering community are summarized，including structural nonlinear models such as geometric nonlinear model and material nonlinear model；aerodynamic nonlinear modeling methods such as piston theoretical model，CFD aerodynamic model，reduced order model of aerodynamic nonlinear model，and local flow piston theory，flutter equation solving methods such as spatial discretization method and reduced order model technology， and two test methods such as wind tunnel test and ground flutter test. The advantages and disadvantages of these research methods are analyzed，and the future research directions of panel flutter technology are progressed.